Hearing Preservation Surgery via Retrosigmoid Approach with Retrolabyrinthine Meatotomy in Small Vestibular Schwannoma - Cazzador, Diego; Borsetto, Daniele; Alexandre, Enrico; Pavone, Chiara; d'Avella, Domenico; Mazzoni, Antonio; Zanoletti, Elisabetta (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives Vestibular schwannomas (VS) extending into the internal auditory canal (IAC) are currently considered as an unfavorable condition for hearing preservation surgery (HPS) via retrosigmoid (RS) approach due to the poor direct visualization of the facial and cochlear nerves course through the IAC and the fundus during microsurgery.Design The operative steps are described in a surgical instructional video.Setting The surgery took place at a tertiary-care center.Participants Patient is a 45-year-old man who was incidentally diagnosed with an extrameatal VS extending for 9 mm into the left cerebellopontine angle (CPA). Hearing function at diagnoses was excellent, with pure tone average (PTA) = 15 dB and speech discrimination score (SDS) = 100% (class A according to the Tokyo classification) and minimal impairments on auditory brainstem response (ABR). Given these preoperative features in small VS, hearing was the main function to look into in the treatment planning. Initial observation or HPS were proposed.Results The patient underwent surgical excision for HPS via RS approach combined with retrolabyrinthine meatotomy (RLM). RLM enables the complete exposure of the IAC to the fundus, after drilling the bony surface of the posterior IAC wall, under guidance of the anatomical landmarks, namely, the endolymphatic duct, the blue lines of the posterior, and superior semicircular canals, and common crus. Nor intra-, neither postoperative complications occurred. Histologic examination confirmed the diagnosis of VS. A 3-month short-term follow-up revealed a class B hearing function with PTA = 30 dB, SDS = 100%, and normal facial nerve status.Conclusions RLM via RS approach proved to be effective for HPS, enabling the full course of the facial and cochlear nerves through the IAC to be directly exposed.The link to the video can be found at: https://youtu.be/KC1S4pxpLCk.
Keywords: acoustic neuroma; hearing preservation surgery; retrolabyrinthine meatotomy; retrosigmoid approach; vestibular schwannoma